2018
DOI: 10.1111/jan.13733
|View full text |Cite
|
Sign up to set email alerts
|

Perceived burden among spouse, adult child, and parent caregivers

Abstract: Because cognitive challenges of care recipient are associated with greater perceived burden and high quality of support with lower burden among most of the caregiver groups, high-quality tailored nursing interventions will be needed especially for the caregivers of the most frail care recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
7
26
0
Order By: Relevance
“…Both Ransmayr et al's [46] and Lethin et al's [45] longitudinal studies and Laporte Uribe et al's cross-sectional studies [43] incorporated patient's behavioural problems such as agitation and aggression in their research, and this proved to be positively related to caregiver burden. These factors Besides behaviour, three articles, both longitudinal and cross-sectional, reported on care recipients' cognitive capacity [45,48,55]. From the research in these articles, it becomes apparent that the patient's cognitive status indeed has predictive value for caregiver burden; reduced cognitive function in the recipient leads to higher burden.…”
Section: General Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Ransmayr et al's [46] and Lethin et al's [45] longitudinal studies and Laporte Uribe et al's cross-sectional studies [43] incorporated patient's behavioural problems such as agitation and aggression in their research, and this proved to be positively related to caregiver burden. These factors Besides behaviour, three articles, both longitudinal and cross-sectional, reported on care recipients' cognitive capacity [45,48,55]. From the research in these articles, it becomes apparent that the patient's cognitive status indeed has predictive value for caregiver burden; reduced cognitive function in the recipient leads to higher burden.…”
Section: General Stressorsmentioning
confidence: 99%
“…Five studies, both longitudinal and cross-sectional, included social support in their research [43,44,50,51,55]. It was found that a higher quality of support, both formal and informal, for the caregiver is associated with lower burden, whereas unmet needs for health and social services contribute to caregiver burden [55]. Moreover, Hsu et al's cross-sectional research [50] referred to the importance of social support aimed at the patient leading to lower caregiver burden.…”
Section: Social Support As Moderatormentioning
confidence: 99%
“…76 Despite the many benefits of older adults living at home, the caregivers often feel burdened by their many responsibilities and the added stress of taking care of a loved one. [77][78][79][80] A recent systematic review indicated that when older, community-dwelling adults present with swallowing difficulties, caregivers share this burden. 81 More specifically, spouses of older adults with dysphagia tend to suffer from emotional burden, while adult, child caregivers of aging parents have cited feeling both emotional and physical burden.…”
Section: Clinical Swallow Examinationmentioning
confidence: 99%
“…One of the factors that influence the caregiving burden is stress (12). Another factor associated with the caregiving burden was the quality of social support (13). The higher quality of social support received the result in the lower caregiving burden (13).…”
Section: Caregiving Burdenmentioning
confidence: 99%
“…Another factor associated with the caregiving burden was the quality of social support (13). The higher quality of social support received the result in the lower caregiving burden (13). Another factor associated with the caregiving burden is the spirituality of caregivers.…”
Section: Caregiving Burdenmentioning
confidence: 99%